Dlaczego Krasiński nazwał księdza Jełowickiego „karłem”? - Fiećko, Jerzy (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
In this article, the author attempts to discover the reasons why in 1848, at the peak of the Springtime of the Peoples, the romantic writer Zygmunt Krasiński repeatedly called a Polish friar Aleksander Jełowicki a “squirt” in the moral, political and every other sense. Krasiński did so in his letters to Delfina Potocka, his lover and Jełowicki’s good acquaintance. Prior to becoming a Resurrectionist in the 1840s, Jełowicki participated in the November Uprising and was a prominent figure of the Great Emigration in Paris, especially as an opinion publicist and publisher (also of Krasiński’s works). In order to answer the question asked in the title, the author traced the earlier history of the relationship between the poet and the friar, created Jełowicki’s psychological, spiritual and intellectual portrait, and devoted significant attention to his moral teachings (on marital issues, among other things) expressed from the position of a dogmatic Catholic priest. As a result, the author proposed a hypothesis, although one lacking definitive proof, that apart from the significant political, dogmatic and religious differences between the two men, Krasiński’s violent reaction could have been caused by the passionate Resurrectionist’s attempts at interfering in his private life. That is because Krasiński had been living in a love triangle for years, sharing his life with Delfina Potocka and his wife Eliza, with no intention of changing this state of affairs, and Jełowicki had a reputation for giving unsolicited advice on people’s private lives. The final part of this sketch describes the later stages of the relationship, which changed after Zygmunt’s relationship with Delfina lost its erotic character – Jełowicki accompanied Krasiński at his deathbed and left a credible account of his passing.